2016
DOI: 10.1136/annrheumdis-2016-209131
|View full text |Cite
|
Sign up to set email alerts
|

Real-world comparative risks of herpes virus infections in tofacitinib and biologic-treated patients with rheumatoid arthritis

Abstract: Objective To evaluate the risks of herpes zoster (HZ) and herpes simplex virus infection (HSV) associated with tofacitinib compared to biologic agents among patients with rheumatoid arthritis (RA). Methods Using health plan data from 2010–2014, RA patients initiating tofacitinib or biologics with no history of HZ or HSV were identified. Incident cases of HZ or HSV within this cohort were identified. Crude incidence rates were calculated by drug exposure. Cox proportional hazards models evaluated the adjusted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
131
3
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 237 publications
(163 citation statements)
references
References 19 publications
(19 reference statements)
13
131
3
8
Order By: Relevance
“…RA itself represents an independent risk factor for reactivation of VZV, followed by age and the use of prednisone, and the risk of herpes zoster infections in patients treated with tofacitinib is further increased by concomitant use of steroids and methotrexate . A comparison of RA patients treated with tofacitinib versus other biological therapies showed that the rate of zoster associated with tofacitinib was approximately double that was observed in patients using biologics . The exact mechanism by which VZV reactivation occurs in the context of JAK inhibition is unclear; however, inhibition of antiviral actions mediated by interferon signaling would seem a likely explanation.…”
Section: Side Effects Of First Generation Jakinibsmentioning
confidence: 99%
“…RA itself represents an independent risk factor for reactivation of VZV, followed by age and the use of prednisone, and the risk of herpes zoster infections in patients treated with tofacitinib is further increased by concomitant use of steroids and methotrexate . A comparison of RA patients treated with tofacitinib versus other biological therapies showed that the rate of zoster associated with tofacitinib was approximately double that was observed in patients using biologics . The exact mechanism by which VZV reactivation occurs in the context of JAK inhibition is unclear; however, inhibition of antiviral actions mediated by interferon signaling would seem a likely explanation.…”
Section: Side Effects Of First Generation Jakinibsmentioning
confidence: 99%
“…Although there has been some controversy around the level of HZ risk associated with biologics for inflammatory disease, there appears to be strong evidence suggesting an increased risk with monoclonal tumor necrosis factor‐α inhibitors, and particularly with infliximab . However, an analysis of US health plan data suggested that the HZ risk associated with tofacitinib in rheumatoid arthritis patients was approximately double that with biologics . An increased incidence of HZ infection in Japanese patients receiving biologic treatment for psoriasis, above that observed in the general population, has also been reported …”
Section: Discussionmentioning
confidence: 99%
“…Preliminary data from phase II and III randomised controlled trials of the Janus Kinase (JAK) inhibitor tofacitinib in RA have shown an increased risk of uncomplicated zoster [34], recently estimated as double that of other biologics [35].…”
Section: Epidemiology Of Infection and Immunitymentioning
confidence: 99%